INTEGRATING TRI HITA KARANA VALUES TO ENHANCE INCLUSIVE EDUCATION QUALITY FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS - I Putu Suamba Adi Putra; I Gede Suwindia; I Made Sedana (Universitas Islam Negeri Mataram, 2026)
This study examines how integrating cultural and spiritual values can enhance the quality of inclusive education for students with special educational needs. Rather than focusing solely on academic outcomes, this research emphasizes a holistic educational approach grounded in the Balinese philosophy of Tri Hita Karana, which promotes harmony between humans and God (parahyangan), among humans (pawongan), and with the natural environment (palemahan). A qualitative case study design was employed at SLB Negeri 1 Buleleng, involving school leaders, teachers, students, and parents. Data were gathered through observations, semi-structured interviews, and document analysis, and validated through triangulation. The data were analyzed through an interactive process consisting of data condensation, data display, and conclusion drawing. The findings indicate that integrating Tri Hita Karana values contributes to improving inclusive education by fostering students’ spiritual awareness, enhancing social collaboration, and strengthening environmental responsibility. These dimensions collectively support the creation of a learning environment that is adaptive, inclusive, and responsive to diverse student needs. This study underscores the importance of embedding local wisdom in educational practices to promote both character development and sustainable educational quality.